ABOUT QUESHION FOR INTERNATIONAL TARIFFES - A. N. Semenikhina (Научный вестник МГТУ ГА)
In this paper the classifications of international airconveyance and tariffs are reduced. Rule of participation in agreements about international tariffs is formulated as mathematical.